Makan Besaprah: Pesan Dakwah dalam Bingkai Tradisi pada Masyarakat Melayu Sambas, Kalimantan Barat - mualimin mualimin (Fakultas Ushuluddin Adab dan Dakwah IAIN Metro-Lampung, 2020)
This study aims to analyze the message of da'wah in the tradition of besaprah (eating together). This research is a qualitative interpretive paradigm. Data were collected in three ways, through observation, interviews, and document studies. While the method used to analyze data is the semiotics method. Based on the analysis that has been done, can be concluded that the teachings of Islam are conveyed through cultural symbols that are packaged properly in the tradition of besaprah. The message of da'wah in the tradition of besaprah is conveyed through cultural symbols. In general the message of da'wah can be divided into three aspects of Islamic teachings. First, the message of faith is related to monotheism and the pillars of faith. Second, the message of sharia is related to observance of implementing Islamic teachings in daily life. Third, the moral message related to friendship, mutual help, glorify humans, and equality between human beings. Keywords : Da'wah Message, Makan Besaprah, Sambas Malay